A high-intensity photothermal response surface lubricating hydrogel and preparation method thereof
By adding thermally responsive polymers and polydopamine nanoparticles to the covalent network hydrogel, a high-intensity photothermal responsive surface lubricating hydrogels was prepared, which solved the problem of the lack of high intensity and adjustable lubricity of the photothermal responsive hydrogels in the prior art, and achieved efficient lubricating effect under near-infrared light conditions.
Patent Information
- Application Number
- CN202210549140.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-05-20
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2042-05-20
AI Technical Summary
The existing photothermal response hydrogels lack high intensity and adjustable lubricating properties under near-infrared light irradiation, making it difficult to meet the application needs of medicine and electronic sensing.
High-intensity photothermal-responsive surface lubricating hydrogel is prepared by adding polymers with thermally responsive substances and polydopamine nanoparticles with photothermal effects to the covalent network hydrogel system.
It realizes the regulation of the surface lubricating properties of the material under external near-infrared light conditions, has high mechanical strength and responsiveness, and is suitable for bionic cartilage replacement materials.
Smart Images

Figure CN114933716B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of photothermal response hydrogels, and specifically relates to a high-intensity photothermal response surface lubricating hydrogel and a preparation method thereof. Background Art
[0002] As a soft material, hydrogel can be highly deformed under external force and respond to external stimuli due to its high water content. It can be used in the fields of medicine and tissue engineering. At present, a variety of stimulus-responsive hydrogels have been prepared, such as light-responsive hydrogels, temperature-responsive hydrogels, mechanical-responsive hydrogels, pH-responsive hydrogels, electric-field-responsive hydrogels, gas-responsive hydrogels, etc. Photothermal responsive hydrogels actually respond to near-infrared light. As a common light source, near-infrared light acts on the surface of the material in a non-contact manner, and the power of near-infrared light can be adjusted to achieve a wider range of regulation. It is a convenient and practical external stimulus method. High-intensity photothermal responsive hydrogel materials partially undergo gel-sol transformation under near-infrared light irradiation, forming a state containing coexistence of gel and sol, and when the near-infrared light is turned off, the overall hydrogel becomes a gel state. This dynamic process is accompanied by the appearance and disappearance of a liquid layer, and the appearance of a liquid layer promotes the reduction of the friction coefficient of the hydrogel surface. At the same time, in order to give it mechanical properties, the dynamic response part is incorporated into the covalent network part, which can achieve high strength while also having controllable lubricating properties. Therefore, photothermal responsive surface lubricating hydrogel is expected to be used in medicine and electronic sensing. Summary of the invention
[0003] The purpose of the present invention is to provide a high-intensity photothermal response surface lubricating hydrogel and a preparation method thereof. The hydrogel has good mechanical properties and can regulate the lubrication properties of the material surface under external near-infrared light conditions.
[0004] The present invention first provides a method for preparing a high-intensity photothermal responsive surface lubricating hydrogel, the steps of which are as follows:
[0005] Step 1: Add polymer monomer 2 to polymer monomer 1, heat to 50-90°C, then add a cross-linking agent, and continue to heat to 50-90°C and stir for 3-8 hours to obtain a solution; polymer monomer 1 and polymer monomer 2 are different;
[0006] The polymer monomer 1 is selected from polyvinyl alcohol, natural rubber, polyacrylamide or polyacrylate;
[0007] The polymer monomer 2 is selected from polyethylene glycol, natural polymer, polyacrylamide or polyacrylate;
[0008] Step 2: Mix water, anhydrous ethanol and ammonia water to obtain a first solution, add the dopamine hydrochloride solution to the first solution for reaction to obtain polydopamine nanoparticles, and dissolve them in water to obtain a polydopamine aqueous solution;
[0009] Step 3: adding the monomer with thermal responsive solid-liquid change and the polydopamine aqueous solution of step 2 to the solution of step 1 and stirring to obtain a hydrogel solution;
[0010] Step 4: Inject the hydrogel solution of step 3 into the mold, freeze it, and then place it at room temperature until the surface temperature of the hydrogel reaches room temperature. Repeat 3-5 times to obtain a high-intensity photothermal responsive surface lubricating hydrogel.
[0011] Preferably, in the polymer monomer 1, the polyvinyl alcohol is polyvinyl alcohol or polyvinyl acetate; the natural gum is gelatin, carrageenan, gellan gum, sodium alginate, agarose, collagen or hyaluronic acid; the polyacrylamide or polyacrylate polymer is poly-N,N-dimethylacrylamide, polyacrylamide, polyacrylic acid, polyhydroxyethyl acrylate, poly(2,2-disulfonyl-4,4-benzidine terephthalamide) or poly(sodium 2-acrylamido-2-methylpropane sulfonate).
[0012] Preferably, in the polymer monomer 2, the polyethylene glycol is polyethylene glycol, polyethylene glycol diethyl ester or polyethylene glycol glycidyl ether; the natural polymer is gelatin, collagen, carboxymethyl cellulose, α-cyclodextrin, β-cyclodextrin, acrylamide, gellan gum, chitosan, agarose, sodium hyaluronate, κ-carrageenan or sodium alginate; the polyacrylamide or polyacrylate is sodium acrylate, acrylyl glycinamide, polyethylene glycol diacrylate, poly (2-acrylamido-2-methyl-1-propanesulfonic acid), poly (2,2-disulfonyl-4,4-benzidine terephthalamide), poly (sodium 2-acrylamido-2-methylpropanesulfonate), four-arm polyethylene glycol, polyacrylic acid, 2,2,2-trifluoroethyl acrylate or poly 2-hydroxyethyl methacrylate.
[0013] Preferably, the cross-linking agent in step 1 is glutaraldehyde, boric acid, borax, genipin, N,N-methylenebisacrylamide or ethylene glycol diethyl ester.
[0014] Preferably, the mass ratio of the polymer monomer 1 to the polymer monomer 2 is 4:1-9:1.
[0015] Preferably, in step 2, the volume ratio of water, anhydrous ethanol and aqueous ammonia is 90:40:1.
[0016] Preferably, the reaction temperature of step 2 is room temperature and the reaction time is 24-36 hours.
[0017] Preferably, the monomer having a thermally responsive solid-liquid change in step 3 is polyisopropylacrylamide, gelatin, PEG, agarose or carrageenan.
[0018] Preferably, in the step three, the mass ratio of the monomer having a thermally responsive solid-liquid change to the polydopamine nanoparticles in the polydopamine aqueous solution is (300-725):(10-200).
[0019] The present invention also provides a high-intensity photothermal response surface lubricating hydrogel obtained by the above preparation method.
[0020] Beneficial effects of the present invention
[0021] The purpose of the present invention is to provide a high-intensity photothermal response surface lubricating hydrogel and a preparation method thereof, wherein a polymer having a thermal response substance and polydopamine (PDA) nanoparticles having a photothermal effect are added to a covalent network hydrogel system prepared by a freeze-thaw method, and the covalent network hydrogel system provides strong mechanical properties to prevent the hydrogel from being damaged. When the polymer having a thermal response substance and the dopamine part are subjected to an external near-infrared light, the surface temperature of the hydrogel increases, prompting the polymer molecules having the thermal response substance to change from gel to sol, and a sol-gel transition occurs on the surface of the hydrogel, and the polymer having the thermal response substance that is disassembled forms a lubricating layer on the surface of the hydrogel, so that the friction coefficient of the surface of the hydrogel material is greatly reduced. This cartilage biomimetic hydrogel having high mechanical strength and responsiveness can realize the regulation of the lubrication properties of the material surface under the condition of external near-infrared light, and is expected to be helpful in bionic cartilage substitute materials. The preparation process of the material is simple, and it can be prepared by repeated freezing and thawing, and this economical, green and simple method has reference significance for large-scale industrial preparation, medical field, and tissue engineering field. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is an optical photograph of the photothermal responsive surface lubricating hydrogel of polydopamine / gelatin-polyvinyl alcohol / polyethylene glycol in Example 1.
[0023] Figure 2 This is a scanning electron microscope image of the high-strength polydopamine / gelatin-polyvinyl alcohol / polyethylene glycol photothermal responsive surface lubricating hydrogel prepared in Example 1 after freeze-drying.
[0024] Figure 3 This is a microscope liquid film display of the high-strength polydopamine / gelatin-polyvinyl alcohol / polyethylene glycol photothermal responsive surface lubricating hydrogel prepared in Example 1.
[0025] Figure 4This is a curve diagram of the assembly and disassembly fracture strength of the high-strength polydopamine / gelatin-polyvinyl alcohol / polyethylene glycol photothermal responsive surface lubricating hydrogel prepared in Example 1.
[0026] Figure 5 This is a friction curve diagram of the assembly and disassembly of the high-strength polydopamine / gelatin-polyvinyl alcohol / polyethylene glycol photothermal responsive surface lubricating hydrogel prepared in Example 1. DETAILED DESCRIPTION
[0027] The present invention first provides a method for preparing a high-intensity photothermal responsive surface lubricating hydrogel, the steps of which are as follows:
[0028] Step 1: Add polymer monomer 2 to the solution of polymer monomer 1, heat to 50-90°C and stir for 1-2h, then add a cross-linking agent, and continue to heat to 50-90°C and stir for 3-8 hours to obtain a solution; the solution of polymer monomer 1 is obtained by adding polymer monomer 1 to ultrapure water, preferably stirring at 20°C to 95°C for 10min to 36h, so that the solid powder is completely dissolved in the water, the concentration of the polymer monomer 1 solution is preferably 0.05 to 0.25g / ml, after the polymer monomer 2 is added to the polymer monomer 1 solution, the concentration of the solution is preferably 0.075 to 0.275g / ml, and the concentration of the cross-linking agent is preferably 0.1 to 1.25μg / ml; the mass ratio of the polymer monomer 1 to the polymer monomer 2 is preferably 4:1-9:1;
[0029] According to the present invention, the polymer monomer 1 is selected from polyvinyl alcohol, natural gum, polyacrylamide or polyacrylate; the polyvinyl alcohol is preferably polyvinyl alcohol and polyvinyl acetate; the natural gum is preferably gelatin, carrageenan, gellan gum, sodium alginate, agarose, collagen or hyaluronic acid; the polyacrylamide or polyacrylate polymer is preferably poly-N,N-dimethylacrylamide, polyacrylamide, polyacrylic acid, polyhydroxyethyl acrylate, poly(2,2-disulfonyl-4,4-benzidine terephthalamide) or poly(2-acrylamide-2-methylpropanesulfonate sodium). The degree of polymerization of polyvinyl alcohol in the polymer monomer 1 is 1700, and the degree of alcoholysis is 97;
[0030] The polymer monomer 2 is selected from polyethylene glycol, natural polymer, polyacrylamide or polyacrylate; the polyethylene glycol is preferably polyethylene glycol, polyethylene glycol diethyl ester or polyethylene glycol glycidyl ether; the natural polymer is preferably gelatin, collagen, carboxymethyl cellulose, α-cyclodextrin, β-cyclodextrin, acrylamide, gellan gum, chitosan, agarose, sodium hyaluronate, κ-carrageenan or sodium alginate; polyacrylamide or polyacrylate is preferably sodium acrylate, acrylyl glycinamide, polyethylene glycol diacrylate, poly (2-acrylamide-2-methyl-1-propanesulfonic acid), poly (2,2-disulfonyl-4,4-benzidine terephthalamide), poly (2-acrylamide-2-methylpropanesulfonic acid sodium), four-arm polyethylene glycol, polyacrylic acid, 2,2,2-trifluoroethyl acrylate or poly 2-hydroxyethyl methacrylate.
[0031] The cross-linking agent is used to promote the cross-linking of monomer 1, and is preferably glutaraldehyde, boric acid, borax, genipin, N,N-methylenebisacrylamide or ethylene glycol diethyl ester.
[0032] Step 2: Mix water, anhydrous ethanol and ammonia water to obtain a first solution, add dopamine hydrochloride solution to the first solution for reaction, the reaction is preferably at room temperature, the reaction time is preferably 24-36 hours, to obtain polydopamine nanoparticles; then add water to obtain a polydopamine aqueous solution; the first solution is preferably prepared by first mixing water and anhydrous ethanol, the mixing and stirring time is preferably 5-15 minutes, and then dripping ammonia water and stirring, the stirring time is preferably 30-60 minutes, the mass fraction of ammonia water is preferably 25%, and the volume ratio of water, anhydrous ethanol and ammonia water is preferably 90:40:1;
[0033] The dopamine hydrochloride solution is preferably obtained by adding dopamine hydrochloride to water, and the mass g of the dopamine hydrochloride: the volume ml of water is preferably 0.5:10; after the reaction is completed, the solution is preferably centrifuged, the centrifugal speed is preferably 12000 revolutions per minute, and the centrifugal time is preferably 15 minutes. The product after centrifugation is collected, and the product is rinsed with deionized water and centrifuged again at 12000 revolutions per minute. The above steps are repeated until the supernatant of the centrifugation becomes colorless and transparent, and the centrifuged product and the solution are freeze-dried to obtain polydopamine nanoparticles;
[0034] Step 3: adding the monomer with thermal response solid-liquid change and the polydopamine aqueous solution of step 2 to the solution of step 1 and stirring, the stirring temperature is preferably 80-85°C, and the stirring time is preferably 1-2h to obtain a hydrogel solution; the monomer with thermal response solid-liquid change is preferably polyisopropylacrylamide, gelatin, PEG, agarose or carrageenan; the mass ratio of the monomer with thermal response solid-liquid change and the polydopamine nanoparticles in the polydopamine aqueous solution is preferably (300-725): (10-200);
[0035] Step 4: Inject the hydrogel solution of step 3 into the mold, preferably remove bubbles in the solution by ultrasound for 5-15 minutes, and obtain a shaped hydrogel after freezing. The freezing temperature is preferably -20-25°C, and the freezing time is preferably 8-12 hours. Then place it at room temperature until the surface temperature of the hydrogel reaches room temperature, repeat 3-5 times, and obtain a high-intensity photothermal response surface lubricating hydrogel.
[0036] The present invention also provides a high-intensity photothermal response surface lubricating hydrogel obtained by the above preparation method.
[0037] The present invention is further described below in conjunction with the following embodiments, but the invention is not limited thereto. The raw materials involved in the embodiments are all commercially available.
[0038] Example 1
[0039] Weigh 11.25g of polyvinyl alcohol (degree of polymerization: 1700, degree of alcoholysis: 97%), add 75ml of deionized water, stir at 95℃ for 24h to completely dissolve the solid powder, and cool the solution to room temperature for use. Take 20ml of the above solution, add 0.75g of polyethylene glycol (molecular weight: 4000), stir at 80℃ for 1h, then add 2ml of 15% boric acid solution, and stir at 80℃ for 6h to obtain a solution;
[0040] Weigh 0.5g dopamine hydrochloride and dissolve it in 10ml deionized water. Measure 90ml of deionized water and mix with 40ml of anhydrous ethanol and stir evenly. Add 1ml of 25-30% ammonia water to the solution. After stirring for 30min, inject the dopamine hydrochloride aqueous solution into the ethanol and ammonia solution, and continue stirring and reacting for 24h to obtain a solution. The solution is centrifuged at 12000 rpm for 15min, and the bottom centrifuged product is washed with deionized water. Repeat the centrifugation and washing until the centrifugal supernatant is colorless and transparent. After freeze-drying the supernatant and the centrifugal precipitate, polydopamine nanoparticles are obtained. Weigh 250mg of polydopamine particles and add them to 50ml of water for 10min of ultrasound to obtain a polydopamine aqueous solution.
[0041] 5 ml of polydopamine aqueous solution and 250 mg of gelatin were added to the solution and stirred at 80 ° C for 1 hour to completely dissolve. The dissolved solution was added to the corresponding mold, and the bubbles in the solution were removed by ultrasonication for 5 minutes. Then, it was placed in a refrigerator at -20 ° C for 8 hours and frozen and thawed 3 times to form a gel. The obtained hydrogel is the high-intensity photothermal response surface lubricating hydrogel material described in the present invention. The sample was stored in a constant temperature and humidity chamber.
[0042] The high-strength hydrogel material used in this embodiment is polyvinyl alcohol / polyethylene glycol; the photothermal responsive supramolecular gel material used is polydopamine / gelatin.
[0043] Figure 1 This is an optical photograph of the photothermal responsive surface lubricating hydrogel of polydopamine / gelatin-polyvinyl alcohol / polyethylene glycol in Example 1.
[0044] Figure 2 This is a scanning electron microscope image of the high-intensity polydopamine / gelatin-polyvinyl alcohol / polyethylene glycol photothermal responsive surface lubricating hydrogel prepared in Example 1 after freeze-drying. The model of the scanning electron microscope is HITACHI-SU8020. Before near-infrared light irradiation, the supramolecular part of the hydrogel surface is in an assembled state, showing a smooth surface state (Figure a); after near-infrared light irradiation, the supramolecular part of the hydrogel surface is in a disassembled state, showing a more uniform porous surface distribution (Figure b). The scanning electron microscope characterization images of the high-intensity photothermal responsive surface lubricating hydrogel prepared in the other examples are similar to this.
[0045] Figure 3 This is a microscopic liquid film display of the high-intensity polydopamine / gelatin-polyvinyl alcohol / polyethylene glycol photothermal responsive surface lubricating hydrogel prepared in Example 1. The cross-section of the hydrogel is displayed before near-infrared light irradiation (Figure a), and a liquid layer appears in the cross-section of the hydrogel after near-infrared light irradiation (Figure b). The appearance of the liquid layer is due to the disassembly of polydopamine / gelatin as the supramolecular part, and the gel-sol conversion occurs. The liquid layer exudation diagrams of the high-intensity photothermal responsive surface lubricating hydrogels prepared in the other examples are similar to this.
[0046] Figure 4 The figure is a curve of the assembly and disassembly fracture strength of the high-intensity polydopamine / gelatin-polyvinyl alcohol / polyethylene glycol photothermal responsive surface lubricating hydrogel prepared in Example 1. The hydrogel material was subjected to a fracture experiment using an Instrument Technology universal material testing machine. After near-infrared light irradiation, the supramolecular disassembly occurred, the supramolecular sub-chain binding ability decreased, the molecular chain collapsed, the original structure changed, and the mechanical properties of the hydrogel decreased. The mechanical property graphs of the high-intensity photothermal responsive surface lubricating hydrogel prepared in the other examples are similar to this.
[0047] Figure 5The friction curves of the assembly and disassembly of the high-strength polydopamine / gelatin-polyvinyl alcohol / polyethylene glycol photothermal response surface lubricating hydrogel prepared in Example 1. The surface lubrication behavior of the hydrogel was characterized using a TADHR-2 rotational rheometer. The friction coefficient of the hydrogel surface under near-infrared light irradiation is lower than that of the unirradiated hydrogel. The liquid layer ( Figure 3 ), resulting in the hydrogel surface becoming slippery. The tribological performance graphs of the high-intensity photothermal response surface lubrication hydrogels prepared in the other embodiments are similar to this.
[0048] Example 2
[0049] Weigh 11.25g of polyvinyl alcohol (degree of polymerization: 1700, degree of alcoholysis: 97%), add 75ml of deionized water, stir at 95℃ for 24h to completely dissolve the solid powder, and cool the solution to room temperature for use. Take 20ml of the above solution, add 0.65g of agarose, stir at 80℃ for 1h, then add 2ml of 15% boric acid solution, and stir at 80℃ for 6h to obtain a solution;
[0050] Weigh 0.5g dopamine hydrochloride and dissolve it in 10ml deionized water. Measure 90ml of deionized water and mix with 40ml of anhydrous ethanol and stir evenly. Add 1ml of 25-30% ammonia water to the solution. After stirring for 30min, inject the dopamine hydrochloride aqueous solution into the ethanol and ammonia solution, and continue stirring and reacting for 24h to obtain a solution. The solution is centrifuged at 12000 rpm for 15min, and the bottom centrifuged product is washed with deionized water. Repeat the centrifugation and washing until the centrifugal supernatant is colorless and transparent. After freeze-drying the supernatant and the centrifugal precipitate, polydopamine nanoparticles are obtained. Weigh 250mg of polydopamine particles and add them to 50ml of water for 10min of ultrasound to obtain a polydopamine aqueous solution.
[0051] 5 ml of polydopamine aqueous solution and 250 mg of gelatin were added to the solution and stirred at 80 ° C for 1 hour to completely dissolve. The dissolved solution was added to the corresponding mold, and the bubbles in the solution were removed by ultrasound for 5 minutes, and then placed in a refrigerator at -20 ° C for 8 hours and frozen and thawed 3 times to form a gel. The obtained hydrogel is the high-intensity photothermal response surface lubricating hydrogel material described in the present invention. The sample was stored in a constant temperature and humidity chamber.
[0052] The high-strength hydrogel material used in this embodiment is polyvinyl alcohol / agarose; the photothermal responsive supramolecular gel material used is polydopamine / gelatin.
[0053] Example 3
[0054] Weigh 11.25g of polyvinyl alcohol (degree of polymerization: 1700, degree of alcoholysis: 97%), add 75ml of deionized water, stir at 95℃ for 24h to completely dissolve the solid powder, and cool the solution to room temperature for use. Take 20ml of the above solution, add 0.45g of sodium hyaluronate, stir at 80℃ for 1h, then add 2ml of 15% boric acid solution, and stir at 80℃ for 6h to obtain a solution;
[0055] Weigh 0.5g dopamine hydrochloride and dissolve it in 10ml deionized water. Measure 90ml of deionized water and mix with 40ml of anhydrous ethanol and stir evenly. Add 1ml of 25-30% ammonia water to the solution. After stirring for 30min, inject the dopamine hydrochloride aqueous solution into the ethanol and ammonia solution, and continue stirring and reacting for 24h to obtain a solution. The solution is centrifuged at 12000 rpm for 15min, and the bottom centrifuged product is washed with deionized water. Repeat the centrifugation and washing until the centrifugal supernatant is colorless and transparent. After freeze-drying the supernatant and the centrifugal precipitate, polydopamine nanoparticles are obtained. Weigh 250mg of polydopamine particles and add them to 50ml of water for 10min of ultrasound to obtain a polydopamine aqueous solution.
[0056] 5 ml of polydopamine aqueous solution and 250 mg of gelatin were added to the solution and stirred at 80 ° C for 1 hour to completely dissolve. The dissolved solution was added to the corresponding mold, and the bubbles in the solution were removed by ultrasound for 5 minutes, and then placed in a refrigerator at -20 ° C for 8 hours and frozen and thawed 3 times to form a gel. The obtained hydrogel is the high-intensity photothermal response surface lubricating hydrogel material described in the present invention. The sample was stored in a constant temperature and humidity chamber.
[0057] The high-strength hydrogel material used in this embodiment is polyvinyl alcohol / sodium hyaluronate; the photothermal responsive supramolecular gel material used is polydopamine / gelatin.
[0058] Example 4
[0059] Weigh 11.25g of polyvinyl alcohol (degree of polymerization: 1700, degree of alcoholysis: 97%), add 75ml of deionized water, stir at 95℃ for 24h to completely dissolve the solid powder, and cool the solution to room temperature for use. Take 20ml of the above solution, add 1.24g of chitosan, stir at 80℃ for 1h, then add 2ml of 15% boric acid solution, and stir at 80℃ for 6h to obtain a solution;
[0060] Weigh 0.5g dopamine hydrochloride and dissolve it in 10ml deionized water. Measure 90ml of deionized water and mix with 40ml of anhydrous ethanol and stir evenly. Add 1ml of 25-30% ammonia water to the solution. After stirring for 30min, inject the dopamine hydrochloride aqueous solution into the ethanol and ammonia solution, and continue stirring and reacting for 24h to obtain a solution. The solution is centrifuged at 12000 rpm for 15min, and the bottom centrifuged product is washed with deionized water. Repeat the centrifugation and washing until the centrifugal supernatant is colorless and transparent. After freeze-drying the supernatant and the centrifugal precipitate, polydopamine nanoparticles are obtained. Weigh 250mg of polydopamine particles and add them to 50ml of water for 10min of ultrasound to obtain a polydopamine aqueous solution.
[0061] 5 ml of polydopamine aqueous solution and 250 mg of gelatin were added to the solution and stirred at 80 ° C for 1 hour to completely dissolve. The dissolved solution was added to the corresponding mold, and the bubbles in the solution were removed by ultrasound for 5 minutes, and then placed in a refrigerator at -20 ° C for 8 hours and frozen and thawed 3 times to form a gel. The obtained hydrogel is the high-intensity photothermal response surface lubricating hydrogel material described in the present invention. The sample was stored in a constant temperature and humidity chamber.
[0062] The high-strength hydrogel material used in this embodiment is polyvinyl alcohol / chitosan; the photothermal responsive supramolecular gel material used is polydopamine / gelatin.
[0063] Example 5
[0064] Weigh 11.25g of polyvinyl alcohol (degree of polymerization: 1700, degree of alcoholysis: 97%), add 75ml of deionized water, stir at 95℃ for 24h to completely dissolve the solid powder, and cool the solution to room temperature for use. Take 20ml of the above solution, add 0.56g of carboxymethyl cellulose, stir at 80℃ for 1h, then add 2ml of 15% boric acid solution, and stir at 80℃ for 6h to obtain a solution;
[0065] Weigh 0.5g dopamine hydrochloride and dissolve it in 10ml deionized water. Measure 90ml of deionized water and mix with 40ml of anhydrous ethanol and stir evenly. Add 1ml of 25-30% ammonia water to the solution. After stirring for 30min, inject the dopamine hydrochloride aqueous solution into the ethanol and ammonia solution, and continue stirring and reacting for 24h to obtain a solution. The solution is centrifuged at 12000 rpm for 15min, and the bottom centrifuged product is washed with deionized water. Repeat the centrifugation and washing until the centrifugal supernatant is colorless and transparent. After freeze-drying the supernatant and the centrifugal precipitate, polydopamine nanoparticles are obtained. Weigh 250mg of polydopamine particles and add them to 50ml of water for 10min of ultrasound to obtain a polydopamine aqueous solution.
[0066] 5 ml of polydopamine aqueous solution and 250 mg of gelatin were added to the solution and stirred at 80 ° C for 1 hour to completely dissolve. The dissolved solution was added to the corresponding mold, and the bubbles in the solution were removed by ultrasound for 5 minutes, and then placed in a refrigerator at -20 ° C for 8 hours and frozen and thawed 3 times to form a gel. The obtained hydrogel is the high-intensity photothermal response surface lubricating hydrogel material described in the present invention. The sample was stored in a constant temperature and humidity chamber.
[0067] The high-strength hydrogel material used in this embodiment is polyvinyl alcohol / carboxymethyl cellulose; the photothermal responsive supramolecular gel material used is polydopamine / gelatin.
[0068] Example 6
[0069] Weigh 0.5g sodium alginate and add it to 50ml water, stir at room temperature for 8h until the powder is completely dissolved. Take another 0.125g polyethylene glycol and add it to the sodium alginate solution, stir and dissolve for 2h. After it is completely dissolved, centrifuge the precursor solution for 15min to eliminate unreacted bubbles, add 0.1g / ml glutaraldehyde solution, and stir at 80℃ for 1h to obtain a solution;
[0070] Weigh 0.5g dopamine hydrochloride and dissolve it in 10ml deionized water. Measure 90ml of deionized water and mix with 40ml of anhydrous ethanol and stir evenly. Add 1ml of 25-30% ammonia water to the solution. After stirring for 30min, inject the dopamine hydrochloride aqueous solution into the ethanol and ammonia solution, and continue stirring and reacting for 24h to obtain a solution. The solution is centrifuged at 12000 rpm for 15min, and the bottom centrifuged product is washed with deionized water. Repeat the centrifugation and washing until the centrifugal supernatant is colorless and transparent. After freeze-drying the supernatant and the centrifugal precipitate, polydopamine nanoparticles are obtained. Weigh 250mg of polydopamine particles and add them to 50ml of water for 10min of ultrasound to obtain a polydopamine aqueous solution.
[0071] Take another 10 ml of polydopamine solution, add 0.9 g of gelatin into the solution, heat at 80° C. to dissolve for 2 h, and mix the sodium alginate / polyethylene glycol solution and the gelatin / polydopamine solution.
[0072] The solution was added to the corresponding mold, and the mixture was frozen and thawed in a refrigerator at -20°C for 8 hours, and the freezing and thawing was repeated three times. The obtained hydrogel was immersed in a 10 mg / ml calcium chloride solution. The obtained hydrogel is the photothermal responsive surface lubricating hydrogel material described in the present invention. The hydrogel was placed in a constant temperature and humidity chamber for storage.
[0073] The high-strength hydrogel material used in this embodiment is sodium alginate / polyethylene glycol; the photothermal responsive supramolecular gel material used is polydopamine / gelatin.
[0074] Example 7
[0075] Weigh 50 mg of κ-carrageenan and add it to 30 ml of deionized water. Stir at 80°C for 20 min until the κ-carrageenan is completely dissolved in water. Add 12.5 mg of sodium hyaluronate to the solution, adjust the pH to 6.0, add 25 mg of borax, and continue stirring to obtain a transparent and uniform solution.
[0076] Weigh 0.5g dopamine hydrochloride and dissolve it in 10ml deionized water. Measure 90ml of deionized water and mix with 40ml of anhydrous ethanol and stir evenly. Add 1ml of 25-30% ammonia water to the solution. After stirring for 30min, inject the dopamine hydrochloride aqueous solution into the ethanol and ammonia solution, and continue stirring and reacting for 24h to obtain a solution. The solution is centrifuged at 12000 rpm for 15min, and the bottom centrifuged product is washed with deionized water. Repeat the centrifugation and washing until the centrifugal supernatant is colorless and transparent. After freeze-drying the supernatant and the centrifugal precipitate, polydopamine nanoparticles are obtained. Weigh 250mg of polydopamine particles and add them to 50ml of water for 10min of ultrasound to obtain a polydopamine aqueous solution.
[0077] 5 ml of polydopamine solution and 375 mg of gelatin were added to the solution and stirred at 80°C for 1 hour, poured into a mold, and the mold was placed in a refrigerator at -20°C for 8 hours of freeze-thaw, and repeated freeze-thaw for 3 times. The obtained hydrogel is the photothermal responsive surface lubricating hydrogel material of the present invention. The hydrogel was placed in a constant temperature and humidity chamber for storage.
[0078] The high-strength hydrogel material used in this example is κ-carrageenan / sodium hyaluronate; the photothermal responsive supramolecular material used is polydopamine / gelatin.
[0079] Example 8
[0080] Weigh 11.25g of polyvinyl alcohol (degree of polymerization: 1700, degree of alcoholysis: 97%), add 75ml of deionized water, stir at 95℃ for 24h to completely dissolve the solid powder, and cool the solution to room temperature for use. Take 20ml of the above solution, add 0.35g of κ-carrageenan, stir at 80℃ for 1h, then add 2ml of 15% boric acid solution and stir for 6h to obtain a solution;
[0081] Weigh 0.5g dopamine hydrochloride and dissolve it in 10ml deionized water. Measure 90ml of deionized water and mix with 40ml of anhydrous ethanol and stir evenly. Add 1ml of 25-30% ammonia water to the solution. After stirring for 30min, inject the dopamine hydrochloride aqueous solution into the ethanol and ammonia solution, and continue stirring and reacting for 24h to obtain a solution. The solution is centrifuged at 12000 rpm for 15min, and the bottom centrifuged product is washed with deionized water. Repeat the centrifugation and washing until the centrifugal supernatant is colorless and transparent. After freeze-drying the supernatant and the centrifugal precipitate, polydopamine nanoparticles are obtained. Weigh 250mg of polydopamine particles and add them to 50ml of water for 10min of ultrasound to obtain a polydopamine aqueous solution.
[0082] 5 ml of polydopamine solution and 250 mg of gelatin were added to the solution and stirred at 80°C for 1 hour to obtain a solution. The solution was poured into a mold and frozen and thawed in a refrigerator at -20°C for 8 hours, and repeated freezing and thawing for 3 times. The obtained hydrogel is the photothermal responsive surface lubricating hydrogel material of the present invention. The hydrogel was stored in a constant temperature and humidity chamber.
[0083] The high-strength hydrogel material used in this example is polyvinyl alcohol / κ-carrageenan; the photothermal responsive supramolecular materials used are polydopamine and gelatin.
[0084] Example 9
[0085] Weigh 200 mg of carboxymethyl cellulose and 45 mg of agarose, add them into 50 ml of water, reflux at 80° C. for 3 h until the carboxymethyl cellulose and agarose are completely dissolved, add 3 ml of a 10% genipin aqueous solution and stir for 6 h to obtain a solution;
[0086] Weigh 0.5g dopamine hydrochloride and dissolve it in 10ml deionized water. Measure 90ml of deionized water and mix with 40ml of anhydrous ethanol and stir evenly. Add 1ml of 25-30% ammonia water to the solution. After stirring for 30min, inject the dopamine hydrochloride aqueous solution into the ethanol and ammonia solution, and continue stirring and reacting for 24h to obtain a solution. The solution is centrifuged at 12000 rpm for 15min, and the bottom centrifuged product is washed with deionized water. Repeat the centrifugation and washing until the centrifugal supernatant is colorless and transparent. After freeze-drying the supernatant and the centrifugal precipitate, polydopamine nanoparticles are obtained. Weigh 250mg of polydopamine particles and add them to 50ml of water for 10min of ultrasound to obtain a polydopamine aqueous solution.
[0087] 5 ml of polydopamine and 175 mg of polyethylene glycol were added to the solution and stirred at 80°C for 1 hour. The corresponding solution was poured into a mold and placed in a refrigerator at -25°C for 8 hours of freeze-thaw, and the freeze-thaw was repeated three times. The obtained hydrogel is the photothermal response surface lubricating hydrogel of the present invention. The hydrogel was stored in a constant temperature and humidity chamber.
[0088] The high-strength hydrogel material used in this example is carboxymethyl cellulose / agarose; the photothermal responsive supramolecular materials used are polydopamine and polyethylene glycol.
[0089] Example 10
[0090] Weigh 3.0 g of polyhydroxyethyl acrylate and add it to 20 ml of water. Stir at room temperature for 2 h until it is completely dissolved. Add 0.75 g of polyethylene glycol (molecular weight 4000) and stir at 80° C. for 1 h. Then, add 2 ml of 15% boric acid solution and stir at 80° C. for 6 h to obtain a solution.
[0091] Weigh 0.5g dopamine hydrochloride and dissolve it in 10ml deionized water. Measure 90ml of deionized water and mix with 40ml of anhydrous ethanol and stir evenly. Add 1ml of 25-30% ammonia water to the solution. After stirring for 30min, inject the dopamine hydrochloride aqueous solution into the ethanol and ammonia solution, and continue stirring and reacting for 24h to obtain a solution. The solution is centrifuged at 12000 rpm for 15min, and the bottom centrifuged product is washed with deionized water. Repeat the centrifugation and washing until the centrifugal supernatant is colorless and transparent. After freeze-drying the supernatant and the centrifugal precipitate, polydopamine nanoparticles are obtained. Weigh 250mg of polydopamine particles and add them to 50ml of water for 10min of ultrasound to obtain a polydopamine aqueous solution.
[0092] 5 ml of polydopamine aqueous solution and 250 mg of gelatin were added to the solution and stirred at 80°C for 1 hour to completely dissolve. The dissolved solution was added to the corresponding mold and placed in a refrigerator at -20°C for 8 hours of freeze-thaw, and the freeze-thaw was repeated 3 times to form a gel. The obtained hydrogel is the high-intensity photothermal response surface lubricating hydrogel material described in the present invention. The sample was stored in a constant temperature and humidity chamber.
[0093] The high-strength hydrogel material used in this example is polyhydroxyethyl acrylate / polyethylene glycol; the photothermal responsive supramolecular materials used are polydopamine and gelatin.
[0094] Embodiment 11
[0095] Weigh 50 mg of κ-carrageenan and add it to 30 ml of deionized water. Stir at 80°C for 15 min until the κ-carrageenan is completely dissolved in water. Add 12.5 mg of sodium hyaluronate to the solution, adjust the pH to 6.0, add 2 ml of 15% borax solution, and continue stirring for 1 h to obtain a transparent and uniform solution.
[0096] Weigh 0.5g dopamine hydrochloride and dissolve it in 10ml deionized water. Measure 90ml of deionized water and mix with 40ml of anhydrous ethanol and stir evenly. Add 1ml of 25-30% ammonia water to the solution. After stirring for 30min, inject the dopamine hydrochloride aqueous solution into the ethanol and ammonia solution, and continue stirring and reacting for 24h to obtain a solution. The solution is centrifuged at 12000 rpm for 15min, and the bottom centrifuged product is washed with deionized water. Repeat the centrifugation and washing until the centrifugal supernatant is colorless and transparent. After freeze-drying the supernatant and the centrifugal precipitate, polydopamine nanoparticles are obtained. Weigh 250mg of polydopamine particles and add them to 50ml of water for 10min of ultrasound to obtain a polydopamine aqueous solution.
[0097] 5 ml of polydopamine solution and 175 mg of polyethylene glycol were added to the solution at 80°C, stirred for 1 hour, poured into the mold, and the mold was placed in a refrigerator at -20°C for 8 hours of freeze-thaw, and repeated freeze-thaw for 3 times. The obtained hydrogel is the photothermal responsive surface lubricating hydrogel material of the present invention. The hydrogel was placed in a constant temperature and humidity chamber for storage.
[0098] The high-strength hydrogel material used in this embodiment is κ-carrageenan / sodium hyaluronate; the photothermal responsive supramolecular gel material used is polydopamine and polyethylene glycol.
Claims
1. A method for preparing a high-intensity photothermal responsive surface lubricating hydrogel, characterized in that: The steps are as follows: Step 1: Add polymer 2 to the solution of polymer 1, heat to 50-90°C, then add a cross-linking agent to promote cross-linking of polymer 1, continue heating to 50-90°C and continue stirring for 3-8 hours to obtain a solution; polymer 1 and polymer 2 are different; The polymer 1 is selected from polyvinyl alcohol or natural rubber; The polymer 2 is selected from natural polymers; The cross-linking agent in step 1 is glutaraldehyde, boric acid, borax or genipin; Step 2: Mix water, anhydrous ethanol and ammonia water to obtain a first solution, add the dopamine hydrochloride solution to the first solution for reaction to obtain polydopamine nanoparticles, and dissolve them in water to obtain a polydopamine aqueous solution; Step 3: adding the component with thermal response solid-liquid change and the polydopamine aqueous solution of step 2 to the solution of step 1 and stirring to obtain a hydrogel solution; Step 4: inject the hydrogel solution of step 3 into the mold, freeze it, and then place it at room temperature until the surface temperature of the hydrogel reaches room temperature, repeat 3-5 times to obtain a high-intensity photothermal response surface lubricating hydrogel; In the polymer 1, the polyvinyl alcohol is polyvinyl alcohol; the natural gum is gelatin, carrageenan, gellan gum, sodium alginate, agarose, collagen or hyaluronic acid; In the polymer 2, the natural polymer is collagen, carboxymethyl cellulose, α-cyclodextrin, β-cyclodextrin, gellan gum, chitosan, agarose, sodium hyaluronate, κ-carrageenan or sodium alginate; In the step three, the component with thermal response solid-liquid change is gelatin or polyethylene glycol.
2. The method for preparing a high-intensity photothermal responsive surface lubricating hydrogel according to claim 1, characterized in that: The mass ratio of the polymer monomer 1 to the polymer monomer 2 is 4:1-9:
1.
3. The method for preparing a high-intensity photothermal responsive surface lubricating hydrogel according to claim 1, characterized in that: In the step 2, the volume ratio of water, anhydrous ethanol and aqueous ammonia is 90:40:
1.
4. The method for preparing a high-intensity photothermal responsive surface lubricating hydrogel according to claim 1, characterized in that: The reaction temperature of step 2 is room temperature and the reaction time is 24-36 hours.
5. The method for preparing a high-intensity photothermal responsive surface lubricating hydrogel according to claim 1, characterized in that: The mass ratio of the component with thermal response solid-liquid change in step 3 to the polydopamine nanoparticles in the polydopamine aqueous solution is (300-725): (10-200).
6. A high-intensity photothermal responsive surface lubricating hydrogel obtained by the preparation method according to any one of claims 1 to 5.
Citation Information
Patent Citations
Preparation method of room-temperature photo-thermal self-repairing hydrogel
CN110483813A
Lubricating hydrogel material, and preparation method and application thereof
CN110498886A